Prognostic value of the PDW/HDL-C ratio in patients with chest pain symptoms and coronary artery calcification - Qiu, Ya-Jing; Luo, Jun-Yi; Luo, Fan; Tian, Xin-Xin; Zeng, Lu; Zhang, Zhuo-Ran; Li, Xiao-Mei; Yang, Yi-Ning (Frontiers in Cardiovascular Medicine, 2022)
Background Platelet-related parameters and HDL-C have been regarded as the reliable and alternative markers of coronary heart disease (CHD) and the independent predictors of cardiovascular outcomes. Whether the PDW/HDL-C ratio predicts major adverse cardiovascular and cerebrovascular events (MACCEs) in patients complained of chest pain and confirmed coronary artery calcification remains to be investigated. The aim of this study was to investigate the prognostic value of the PDW/HDL-C ratio in patients with chest pain symptom and coronary artery calcification. Methods A total of 5647 patients with chest pain who underwent coronary computer tomography angiography (CTA) were enrolled in the present study. Patients were divided into two groups according to their PDW/HDL-C ratio or whether the MACCEs occurs. The primary outcomes were new-onset MACCEs, defined as the composite of all-cause death, non-fatal MI, non-fatal stroke, revascularization, malignant arrhythmia and severe heart failure. Results During the 89-month follow-up, 304 (5.38%) MACCEs were recorded. The incidence of MACCEs was significantly higher in patients with the PDW/HDL-C ratio > 13.33. The K–M survival curves showed that patients in the high PDW/HDL-C ratio group had significantly lower survival rate than patients in the low PDW/HDL-C ratio group (log-rank test: P < 0.001). Multivariate Cox hazards regression analysis reveals that the PDW/HDL ratio was an independent predictor of MACCEs (HR: 1.604, 95% CI: 1.263-2.035; P < 0.001). Cox regression analysis shows that participants with lower PDW/HDL-C ratio had a higher risk of MACCEs than those in the higher ratio group. The incidence of MACCEs was also more common in PDW/HDL-C ratio > 13.33 group among different severity of coronary artery calcification. Furthermore, adding PDW/HDL-C ratio to the traditional prognostic model for MACCEs improved C-statistic (P < 0.001), the NRI value (11.3% improvement, 95% CI: 0.018-0.196, P = 0.01) and the IDI value (0.7% improvement, 95% CI: 0.003-0.010, P<0.001).